Peningkatan Tingkat Kesiapan Teknologi SEMAR (Statistical Multimedia Based on Multi Representation and Augmented Reality) - Santia, Ika; Ardiana, Ardiana; Pai’pinan, Matius; Palayukan, Hersiyati; Zayyadi, Moh. (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
Abstract: SEMAR (Statistical Multimedia Based on Multi-representation and Augmented Reality) is a digital innovation in the form of learning multimedia that can improve numeracy literacy in statistics learning. SEMAR is a prototype developed from an integrated statistical e-module of multi-representation and augmented reality with Technology Readiness Level (TKT 3) with increased innovation from website-based media to android-based multimedia (TKT 4). The purpose of improving TKT is intended to achieve the novelty of SEMAR products in supporting independent learning of statistics in Indonesia. The TKT improvement method used is through expert validation test techniques and national-scale public tests. Both tests were carried out at seven universities in Indonesia, including Nusantara PGRI University Kediri, PGRI University Madiun, Nahdatul Ulama University Blitar, Madura University, Khairun University Ternate, Cendrawasih University, and Indonesian Christian University Toraja. The results of the validation test show that the average SEMAR feasibility value is 90.92% with a very feasible category, and the average SEMAR user response is 77.87% with a good user response category.